(untitled) (International journal of artificial intelligence, 2025)
The article scientifically analyzed the changes in the biological properties and quality indicators of table grape varieties (Aq Husayni and Husayni Kelin finger) stored using traditional methods in local conditions. During the study, the sugar content, pH environment, and storage period were studied. The results showed a sharp increase in the storage period with an increase in the sugar content in grapes. Also, slight changes in the pH environment were observed during the storage process. The data obtained will serve as a scientific basis for increasing the efficiency of grape storage, improving traditional methods, and expanding export potential.